Optimal Screening for Hereditary Head and Neck Paraganglioma in Asymptomatic SDHx Variant Carriers in the Netherlands - Heesters, Anouk Frederique; Tops, Carli; Potjer, Thomas; Corssmit, Eleonora P.M.; Bayley, Jean-Pierre; Hensen, Erik; Jansen, Jeroen (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background SDHx variant carriers have an increased risk of developing head and neck paraganglioma. The Dutch guidelines state that these patients require lifelong follow-up, but no clear recommendation is made about the frequency of screening.Objective To determine the annual risk of developing head and neck paraganglioma in SDHx variant carriers after a negative initial screening.Methods We conducted a retrospective single-center cohort study in the Netherlands that included 49 SDHA, SDHB, and SDHD variant carriers with a negative first screening and at least one follow-up. The main outcome measure was the annual risk of developing a paraganglioma for the SDHx variants separately.Results Between 2000 and 2022, nine patients developed a paraganglioma all of whom were carriers of a SDHD variant (n = 23). Neither the 24 SDHB-related cases nor the 2 SDHA variant carriers developed a paraganglioma after a median of 4.83 and 5.92 years of follow-up, respectively.Conclusion The 5-year risk for head and neck paragangliomas in pathological SDHx variant carriers is less than 20%. A 5-year interval for screening SDHx carriers seems sufficient to prevent the unnoticed development of head and neck paragangliomas that warrant treatment.
Keywords: paraganglioma; hereditary; SDHA; SDHB; SDHD; screening